WAYS OF DEVELOPING INFRASTRUCTURE FOR REDUCING POVERTY IN THE REGION (CASE OF BUKHARA REGION) - Nazarov , Sh. (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis examines infrastructure development as a key socio-economic mechanism for reducing poverty at the regional level, using the case of Bukhara region. The author proposes and tests the original “5I model” (Investments – Infrastructure – Inclusion – Innovation – Income). Through regression analysis of 2019-2024 data for 11 districts, the study quantifies the elasticity of poverty with respect to infrastructure investment and identifies inter-district inequality as a structural driver of poverty.